Effect of alglucosidase alfa dosage on survival and walking ability in patients with classic infantile Pompe disease: a multicentre observational cohort study from the European Pompe Consortium. (January 2022) - Ditters, Imke Anne Maartje; Huidekoper, Hidde Harmen; Kruijshaar, Michelle Elisabeth; Rizopoulos, Dimitris; Hahn, Andreas; Mongini, Tiziana Enrica; Labarthe, François; Tardieu, Marine; Chabrol, Brigitte; Brassier, Anais; Parini, Rossella; Parenti, Giancarlo; et al.
Summary: Background: Enzyme replacement therapy (ERT) with alglucosidase alfa has been found to improve outcomes in patients with classic infantile Pompe disease, who without treatment typically die before the age of 1 year. Variable responses to the standard recommended dosage have led to alternative dosing strategies. We aimed to assess the effect of real-world ERT regimens on survival and walking ability in these patients. Methods: In this observational cohort study, we obtained data collected as part of a collaborative study within the European Pompe Consortium on patients with classic infantile Pompe disease from France, Germany, Italy, and the Netherlands diagnosed between Oct 26, 1998 and March 8, 2019. Eligible patients had classic infantile Pompe disease with a disease onset and proven diagnosis before age 12 months, and a hypertrophic cardiomyopathy. A proven diagnosis of classic infantile Pompe disease was defined as a confirmed deficiency of α-glucosidase in leukocytes or lymphocytes, fibroblasts or muscle, or two pathogenic GAA variants in trans, or both. We collected data on demographics, GAA variants, ERT dosage, age at death, and walking ability. We analysed the effects of ERT dosage on survival and walking ability using Cox regression, Kaplan-Meier curves, and log-rank tests. Findings: We included 124 patients with classic infantile Pompe disease, of whom 116 were treated with ERT (median age at start of treatment 3·3 months [IQR 1·8–5·0, range 0·03–11·8]). During follow-up (mean duration 60·1 months [SD 57·3]; n=115), 36 (31%) of 116 patients died. 39 different ERT dosing regimens were applied. Among the 64 patients who remained on the same dosage, 16 (52%) of 31 patients on the standard dosage (20 mg/kg every other week), 12 (80%) of 15 patients on an intermediate dosage (20 mg/kg per week or 40 mg/kg every other week), and 16 (89%) of 18 patients on the high dosage (40 mg/kg per week) were alive at last follow-up. Survival was significantly improved in the high dosage group compared with the standard dosage group (hazard ratio [HR] 0·17 [95% CI 0·04–0·76], p=0·02). No significant difference in survival was identified between the intermediate dosage group and the standard dosage group (HR 0·44 [0·13–1·51], p=0·19). Of the 86 patients who reached 18 months of age, 44 (51%) learned to walk. Ten (53%) of 19 patients on the standard dosage regimen, six (67%) of nine patients on intermediate dosage regimens, and 14 (93%) of 15 patients on high dosage regimens learnt to walk, but the differences between groups were not statistically significant. Interpretation: Patients with classic infantile Pompe disease treated with the high ERT dosage of 40 mg/kg per week had significantly improved survival when compared with patients treated with the standard recommended ERT dosage of 20 mg/kg every other week. Based on these results, we suggest that the currently registered dosage should be reconsidered. Funding: Prinses Beatrix Spierfonds and Wishdom Foundation.